PEMODELAN SPASIAL KERENTANAN WILAYAH TERHADAP PENYAKIT LEPTOSPIROSIS BERBASIS EKOLOGI - Widayani, Prima; Kusuma, Dyah (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2014)
Leptospirosis is an acute infectious disease that can infect humans and animalscaused by leptospira bacteria and classified as zoonotic pathogens. Outbreaks ofthe disease within a few years has been attacking people in Bantul. In the period2009 to March 2013 there have been 394 cases, based on these facts it isnecessary to mapping disease susceptibility regions to leptospirosis in order todetermine priority areas of treatment and prevention. Spatial pattern analysis ofspread of the disease leptospirosis is done by using a method Nearest NeighborDistance Average. Modelling the ecological mapping units using remote sensingdata to tap environmental data such as land use, soil texture, stream buffers, andthe buffers settlement with the visual interpretation method. Index models areused to create vulnerability models of leptospirosis disease. To test the accuracyof the data model is used the cases of leptospirosis which have plots in study field.Based on accuration test, it showed that there are 76 leptospirosis cases (or92.68%) layed on vulnerable area in Imogiri, Bantul and Jetis District. Spatialdistribution pattern analysis of the leptospirosis cases using average nearestneighbor distance methods showed that the distribution of the cases are groupedwith z score value is - 2.41.